The mystery of Edwin Drood [videorecording (DVD)] - Lawrence, Diarmuid; Rhys, Matthew, 1974-; Merchant, Tamzin; Fox, Freddie, 1989-; Dickens, Charles, 1812-1870 (PBS Home Video, 2012)
John Jasper is haunted and restless. Unhappily settled as choirmaster in the provincial cathedral town of Cloisterham, Jasper finds himself striving for the divine in his music even as he struggles against madness brought on by ennui and opiates. Aware of his unraveling, Jasper believes his salvation may be found in the arms of Rosa, his prized pupil. His only obstacle is her fiance, Edwin Drood - Jasper's nephew.